2011
DOI: 10.1158/0008-5472.sabcs11-s1-8
|View full text |Cite
|
Sign up to set email alerts
|

S1-8: Molecular Signaling Distinguishes Early ER Positive Breast Cancer Recurrences Despite Adjuvant Tamoxifen.

et al.

Abstract: Background: Unlike recurrences with other therapies, ER+ breast cancers (BC) can recur ≥10 yrs after an apparent successful period of adjuvant endocrine therapy. The molecular basis for this pattern of resistance is unresolved. We addressed the hypothesis that early recurrences during tamoxifen (TAM) treatment exhibit different biological characteristics than those that recur years later by assessing for variation in their respective transcriptomes. Methods: Appropriate tumors were identified fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The ratio of two individual mRNAs, HOXB13/IL17BR, has been demonstrated to be a prognostic factor in ER+ and node negative patients, which is the major population giving rise to late recurrences (54, 55). Gene expression signatures that are retrospectively associated with late recurrences have recently been derived by comparing the gene expression profiles of primary tumors of early vs. late recurrences (56, 57), or using dormant cancer cells in experimental systems (58). Whether these signatures can prospectively predict late recurrences remains to be tested.…”
Section: Clinical Challenges Of Er+ Dormancymentioning
confidence: 99%
“…The ratio of two individual mRNAs, HOXB13/IL17BR, has been demonstrated to be a prognostic factor in ER+ and node negative patients, which is the major population giving rise to late recurrences (54, 55). Gene expression signatures that are retrospectively associated with late recurrences have recently been derived by comparing the gene expression profiles of primary tumors of early vs. late recurrences (56, 57), or using dormant cancer cells in experimental systems (58). Whether these signatures can prospectively predict late recurrences remains to be tested.…”
Section: Clinical Challenges Of Er+ Dormancymentioning
confidence: 99%
“…Tumors with mutations in PIK3CA have been shown to be associated with lower recurrence and mortality rates in the late time period [ 13 , 14 ]. Liu and colleagues [ 15 ] analyzed predictors of late relapse in early-stage ER-positive breast cancer, in which differences in the primary tumor tissue in patients with distant relapses occurring early (less than 3 years) versus late (after 7 years) have been compared. A set of genes was identified that were prognostic specifically for early relapse ( CALM1 , CALM2 , CALM3 , SRC , CDK1 , and MAPK1 ), but they also identified genes that appear to predict late relapse ( ESR1 , ESR2 , EGFR , BCL2 , and AR ).…”
Section: Cancer-related Genesmentioning
confidence: 99%